Purposeful search and characteristic of anti-inflammatory activity of sodium (3-R-2-оxo-2Н-[1,2,4]triazino[2,3-c]quinazolin-6-yl)alkylcarboxylates and their halogen containing analogues - V. V. Yakubovska; N. М. Seredinska; О. Yu. Voskoboynik; G. І. Stepanyuk; S. І. Kovalenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2016)
Aim. The approaches for creating novel agents with anti-inflammatory activity among sodium (3-R-2-oxo-2Н-[1,2,4]triazino[2,3-c]quinazolin-6-yl)alkylcarboxylates and their halogen containing analogues were described in presented article.